PERAN UNICEF DALAM MENANGGULANGI ISU PERKAWINAN ANAK DI ETHIOPIA PADA PERIODE 2016-2019 - Muhammad Satria Ramadhan, (2022)
The practice of child marriage is considered to violate the Universal Declaration of Human Rights (UDHR) and various UN covenants such as the United Nations Convention on the Rights of the Child (UNCRC) and the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). Ethiopia still occupies the 15th position with the highest cases of child marriage in the world and there is no firm sanction to deal with the practice of child marriage. UNICEF as an agency of the United Nations acts as an independent actor successfully in collaboration with UNFPA trying to carry out its role as an instrument by developing a Global Program to end Child Marriage and formulating a strategy in influencing Ethiopia to make a National Action Plan (NAP). This thesis aims to explain the correlation between the role of UNICEF as an International Organization (OI) and the issue of child marriage. This study uses qualitative descriptive methods and OI theory to analyze factors and solutions to existing problems and can explain the role of UNICEF. This research results in an analysis that UNICEF has succeeded in assisting Ethiopia with the realization of the new NAP in 2020. The suggestions offered are that UNICEF needs intense supervision so that the NAP can run according to plan and ensure the flow of financial assistance to the parties involved.